Hydrogen cyanide exchange on IAl(HCN)6]3+ - A DFT study - Puchta, Ralph; Alzoubi, Basam; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2009)
The hydrogen cyanide exchange mechanism of [A1(HCN)6] 3+ has been investigated by DFT calculations (B3LYP/6-311 + G **). The calculations provide theoretical evidence that the hydrogen cyanide exchange proceeds via a limiting dissociative (D) mechanism involving a stable five-coordinate intermediate [A1(HCN)5· (HCN)2]3+. The activation energy for the D-mecha-nism is 23.4 kcal · mol-1, which is 2.8 kcal·mol-1 lower than for the seven-coordinate transition state [A1(HCN)2] 3+‡ for the alternative associative (A) pathway. The difference in stability between the two intermediates [A1(HCN)5 · (HCN)2]3+ (12.1 kcal · mol-1) and [A1(HCN)7]3+ (25.7 kcal · mol-1) in comparison to [A1(HCN)6 · (HCN)]3+ is much more pronounced and further supports a limiting dissociative mechanism. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Aluminium; Coordination chemistry; Density functional calculations; HCN exchange